INDEKS VIRUS-VIRUS PEMICU KEMATIAN MASSAL SEBAGAI MEDIA EDUKASI - Rahmah, Fikratul; Arwendria, Arwendria; Hasfera, Dian (UIN Imam Bonjol Padang, 2021)
ABSTRACT This research is motivated by the emergence of the current Covid-19 Virus. With the emergence of Covid-19, there are many public assumptions about viruses that all viruses are considered deadly even though not all viruses are deadly. The weaknesses of society in dealing with their conditions are delays in handling, lack of clear knowledge and information, especially the lack of educational resources or learning media for children on how to deal with a virus outbreak. In fulfilling information, many people see information through the internet, but not all the news that is disseminated is accurate. The purpose of this research is how to design a product in the form of an index book of the viruses that trigger mass death. The index book of the viruses that trigger mass death will later help readers to find out and understand the information that is available in a valid, effective and practical manner. This index book of viruses that trigger mass death is declared valid because it has collaborated with a validator of library scientists and an expert validator in the field of health sciences. The type of research used is Development Research. The stages that are passed in product development are needs analysis, product design, product creation and product trial evaluation. The results of this study show that the book Index of viruses that trigger mass death can be used by readers in understanding the name of the virus, the symptoms it causes, how to prevent it, a brief description and references about these viruses. ABSTRAK Penelitian ini dilatarbelakangi oleh munculnya Virus Covid-19 saat ini. Dengan munculnya Covid-19 banyak asumsi-asumsi masyarakat mengenai virus bahwa semua virus-virus dianggap mematikan padahal tidak semua virus itu yang mematikan. Kelemahan masyarakat dalam menghadapi kondisinya yaitu keterlambatan penanganan, kurangnya pengetahuan serta informasi yang jelas terutama minimnya sumber edukasi atau media pembeljaran untuk anak-anak bagaimana menghadapi suatu wabah virus. Dalam memenuhi informasi banyak masyarakat melihat informasi melaui internet, akan tetapi tidak semua berita yang disebarkan akurat. Tujuan dari penelitian ini yaitu bagaimana merancang produk berupa buku indeks virus-virus pemicu kematian massal. Buku Indeks virus-virus pemicu kematian massal ini nantinya akan membantu pembaca untuk mengetahui dan memahami informasi yang tersedia secara valid, efektif dan Praktis. Buku Indeks Virus-virus pemicu kematian massal ini dinyatakan valid karena sudah berkolaborasi dengan validator ahli ilmu perpustakaan dan Validator Ahli bidang Ilmu kesehatan. Jenis penelitian yang digunakan yaitup penelitian pengembangan (Development Research). tahapan-tahapan yang dilalui dalam pengembangan produk taitu analisis kebutuhan, merancang produk, membuat produk dan evaluasi uji coba produk. Hasil penelitian ini menunjukan buku Indeks virus-virus pemicu kematian massal ini sudah dapat digunakan pembaca dalam memahami tentang nama virus, gejala yang ditimbulkan, bagaimana upaya pencegahanya, deskripsi singkat dan referensi-referesni mengenai virus-virus tersebut. Keywords: Index, Covid-19, Deadly viruses, Education